OCCURRENCE OF THE BRINE-SHRIMP, ARTEMIA SAUNA, IN KARSEWAR ISLAND OFF TUTICORIN, GULF OF MANNAR - Achari, G P Kumaraswamy (Indian Journal of Fisheries, 2011)
Artemia salina is reported from Karsewar island off Tuticorin, Gulf of Mannar.Their probable distribution by flamingos wliich frequently visit Artemia habitat is discussed.